Experimental and thermomechanical analysis of friction stir welding of poly(methyl methacrylate) sheets. (3rd April 2018) - Aghajani Derazkola, H.; Simchi, Abdolreza
ABSTRACT: In the present work, the feasibility of friction stir welding (FSW) of poly(methyl methacrylate) sheets was studied experimentally and theoretically by employing thermomechanical simulations. The effect of processing parameters including tool plunge depth, tilt angle, tool rotational speed ( w ), and transverse velocity ( v ) was investigated to determine suitable conditions to attain sound and defect-free joints. It is shown that a low tool plunge depth of 0.2 mm and a tilt angle of 2° provide suitable material flow to gain sound joints. By controlling the heat input into stir zone by increasing the tool rotational speed and decreasing linear velocity, the formation of defects can be minimised. Mechanical examinations in both longitudinal (LS) and transverse (TS) directions indicate that the highest joint strength of 57 MPa (for LS) and 42 MPa (for TS) are obtained at processing conditions of w  = 25 mm min −1 and v  = 1600 rev min −1 . The measured tensile strengths are 81 and 60% of the base polymer, respectively.